Evaluation of oral submucous fibrosis using ultrasonographic technique: A new diagnostic tool - K Manjunath; P C Rajaram; T R Saraswathi; B Sivapathasundharam; B Sabarinath; D Koteeswaran; C Krithika (Wolters Kluwer Medknow Publications, 2011)
Aim: The aim of this study is to evaluate oral submucous fibrosis (OSMF) by clinical and histopathological examination, and compare the results with those from ultrasonographic technique. Materials and Methods: 30 clinically diagnosed OSMF patients were subjected to both ultrasonographic and histopathological evaluation before treatment. Later, only ultrasonographical examination was done during 4 th and 8 th week of treatment. Prognosis of the lesion for the treatment was evaluated. Peak systolic velocity (PSV) of blood in the lesional area was statistically analyzed. 10 normal individuals without any mucosal lesions were considered as the control group. Results: In normal individuals, ultrasonography delineates normal mucosa with uniform fine mottled appearance with interspersed hypoechoic areas. Color Doppler and spectral Doppler depicts uniform distribution of blood vessels and normal peak systolic velocity of blood respectively. All OSMF patients were diagnosed upon clinical and histopathological examination. Clinical examination revealed 14 individuals with unilateral palpable fibrotic bands and 16 individuals with bilateral fibrotic bands whereas, ultrasonographic evaluation revealed 6 individuals with unilateral fibrotic bands and 24 individuals were with bilateral fibrotic bands, which was statistically significant. Ultrasonography demonstrated number, length and thickness of the fibrotic bands. Color Doppler and spectral Doppler showed decreased vascularity and PSV in lesional area. Prognosis evaluation revealed 25 cases of good prognosis and 5 cases were showed poor prognosis. Wilcoxon Signed Ranks Test revealed no significant difference of PSV was seen in poor prognosis patients. Conclusion: Ultrasonography is a non-invasive diagnostic tool for OSMF. It could be a better diagnostic tool compared to clinical and histopathological examination.